Estimating Canadian sodium intakes and the health impact of meeting national and WHO recommended sodium intake levels: A macrosimulation modelling study - Flexner, Nadia; Christoforou, Anthea K.; Bernstein, Jodi T.; Ng, Alena P.; Yang, Yahan; Fernandes Nilson, Eduardo A.; Labonté, Marie-Ève; L'Abbe, Mary R. (Public Library of Science (PLoS), 2023)
Background Cardiovascular diseases (CVDs) are the second leading cause of total deaths in Canada. High blood pressure is the main metabolic risk factor for developing CVDs. It has been well established that excess consumption of sodium adversely affects blood pressure. Canadians' mean sodium intakes are well above recommended levels. Reducing dietary sodium intake through food reformulation has been identified as a cost-effective intervention, however, dietary sodium intake and the potential health impact of meeting recommended sodium intake levels due to food reformulation have not been determined in Canada. Objective This study aimed to 1) obtain robust estimates of Canadians' usual sodium intakes, 2) model sodium intakes had foods been reformulated to align with Health Canada's sodium reduction targets, and 3) estimate the number of CVD deaths that could be averted or delayed if Canadian adults were to reduce their mean sodium intake to recommended levels under three scenarios: A) 2,300 mg/d-driven by a reduction of sodium levels in packaged foods to meet Health Canada targets (reformulation); B) 2,000 mg/d to meet the World Health Organization (WHO) recommendation; and C) 1,500 mg/d to meet the Adequate Intake recommendation. Methods Foods in the University of Toronto's Food Label Information Program 2017, a Canadian branded food composition database, were linked to nationally representative food intake data from the 2015 Canadian Community Health Survey-Nutrition to estimate sodium intakes (and intakes had Health Canada's reformulation strategy been fully implemented) The Preventable Risk Integrated ModEl (PRIME) was used to estimate potential health impact. Results Overall, mean sodium intake was 2758 mg/day, varying by age and sex group. Based on 'reformulation' scenario A, mean sodium intakes were reduced by 459 mg/day, to 2299 mg/ day. Reducing Canadians' sodium intake to recommended levels under scenarios A, B and C could have averted or delayed 2,176 (95% UI 869-3,687), 3,252 (95% UI 1,380-5,321), and 5,296 (95% UI 2,190-8,311) deaths due to CVDs, respectively, mainly from ischaemic heart disease, stroke, and hypertensive disease. This represents 3.7%, 5.6%, and 9.1%, respectively, of the total number of CVDs deaths observed in Canada in 2019. Conclusion Results suggest that reducing sodium intake to recommended levels could prevent or postpone a substantial number of CVD deaths in Canada. Reduced sodium intakes could be achieved through reformulation of the Canadian food supply. However, it will require higher compliance from the food industry to achieve Health Canada's voluntary benchmark sodium reduction targets.